Zdrowie i choroba z perspektywy osoby wierzącej na przykładzie poezji Konstancji Benisławskiej = Health and disease from the perspective of a believer, based on the poetry of Konstancja Benisławska - Gorzelana, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Konstancja Benisławska in the volume of poems "Songs sung to oneself" (1776) presents a view of God and herself, and the outside world from the perspective of a believer. Health and illness are also shown from this perspective. In fact, the poet, like other enlightened artists, assumed that health was a desirable value and illness was an anti-value. A detailed analysis of the contexts of the use of the lexemes health and illness allows us to assume, however, that health, although valued by people, is not an absolute value, because the salvation of the soul is more important than health. For this reason, illness can be accepted as long as it becomes a condition for the attainment of salvation.
Keywords: Benisławska, Konstancja (1747-1806); zdrowie; choroba; poezja religijna; oświecenie; health; illness; religious poetry; Enlightenment